2019
DOI: 10.21873/invivo.11594
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Neoadjuvant Versus Adjuvant Chemotherapy in Hispanic/Latino (H/L) Women With Local or Locally Advanced Triple-negative Breast Cancer (TNBC)

Abstract: Background/Aim: The aim of the study was to investigate the efficacy of neoadjuvant and chemotherapy (NACT) and adjuvant chemotherapy (ACT) in Hispanic/Latino (H/L) women with TNBC. Patients and Methods: We reviewed the charts of patients with TNBC, stages I-III, treated at TTUHSC from 2006 to 2016. Overall survival (OS) and recurrence-free survival (RFS) were estimated and compared between the treatment groups. Kaplan-Meier curve and Cox proportional hazards regression analyses were conducted to estimate unad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Table 1 and table 2 presents , and heterogeneity was detected in these data (I 2 =96% P<0.01). Three studies reported the breast conserving surgery rate, from which we found that the breast conserving rate after NACT was lower than ACT (RR = 0.84;95% CI = 0.57-1.23; P =0.37) [12,14,20] (Figure 3), and heterogeneity was detected in these data (I 2 =82%, P=0.004)…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Table 1 and table 2 presents , and heterogeneity was detected in these data (I 2 =96% P<0.01). Three studies reported the breast conserving surgery rate, from which we found that the breast conserving rate after NACT was lower than ACT (RR = 0.84;95% CI = 0.57-1.23; P =0.37) [12,14,20] (Figure 3), and heterogeneity was detected in these data (I 2 =82%, P=0.004)…”
Section: Discussionmentioning
confidence: 92%
“…Signi cant heterogeneity existed among the studies (I 2 =88%, P<0.000001). Unlike TNBC patients who received ACT those with RD who were put on NACT had worse OS (HR = 1.18; 95%CI = 1.09-1.28; P<0.0001), while those who achieved pCR following NACT had signi cant OS bene ts (HR = 0.53; 95%CI = 0.29-0.98; P=0.04) in the studies of Clifton, Fisher, Bagegni and Philipovskiy [12,13,19,20]. Heterogeneity did not exist among the included studies as shown in Figure 4.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations